Fuzzy Single Depot mTSP Model using Robust Ranking Technique for Handling Deposit Carrying Bank - Rahmawati, Rahmawati; Lubis, Fitriani Surayya; Efendi, Riswan; Resta, Anneke De (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Multiple Traveling Salesman Problem (mTSP) of assignment-based consists of two types, namely the single-depot and multi-depot. This study aims to develop a single-depot mTSP assignment-based model with fuzzy travel cost form. The single-depot mTSP model above was formulated using an objective function with trapezoidal fuzzy-coefficient form. The fuzzy forms above were converted into crisp using the Robust Ranking Technique for getting an optimal solution. The developed model above was applied to handle deposit-carrying problem at Mandiri Bank with 20 branches in Pekanbaru, Riau Province, Indonesia. In this problem, the main objective is to minimize the total travel cost by bank’s salesmen from initial depot to all destination branches. The result indicated that the developed fuzzy single-depot mTSP model is capable to determine the minimum total cost above into IDR 70,980.00 with m= 4 salesmen,the upper boundand the lower bound . This developed model could be considered and enhanced in handling deposing-carrying problem from another sectors.